Analisis Manajemen Operasional dalam Meningkatkan Kualitas Layanan Pelanggan pada Warung Madura di Purwokerto - Rachmawati, Desi; Syahrinullah, Syahrinullah (Pascasarjana Universitas Muhammadiyah Mamuju, 2024)
This study aims to analyse operational management in improving customer service quality at Warung Madura in Purwokerto. With the increasingly fierce competition in the culinary industry, service quality is a key factor in attracting and retaining customers. This research uses a qualitative method with a case study approach on several Warung Madura located in Purwokerto. Data was collected through in-depth interviews with stall owners, direct observation. The results showed that the implementation of good operational management, such as raw material stock management, and employee training, has a positive impact on the quality of service perceived by customers. Customers feel more satisfied with the fast service, cleanliness of the stall, and friendliness of the employees. In addition, the study also found that innovations in menus and customisation to local preferences can increase the attractiveness of stalls. In conclusion, improving overall operational management can be an effective strategy to improve the quality of customer service at Warung Madura in Purwokerto, which in turn can increase customer loyalty and the competitiveness of the stall